2009
DOI: 10.1007/s11845-009-0294-8
|View full text |Cite
|
Sign up to set email alerts
|

Sudden cardiac death in the young: a 1-year post-mortem analysis in the Republic of Ireland

Abstract: The national incidence of SCD was 5.59 males and 0.78 females (3.18 overall) per 100,000 males and females aged 14-35, respectively, in 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…To our knowledge, no other study has looked at regional differences in autopsy rates among young sudden unexpected death cases, but one previous study from Ireland reported an autopsy rate in young sudden unexpected death cases to be 76%, which is similar to ours, 75% [1,4]. In our study of SCD in the young, we found the incidence rate to be higher than previously reported (2.8 per 100,000 person-years vs. 1.0-1.9 per 100,000 personyears in Italy, Netherlands, and UK) when including the non-autopsied cases [1,[21][22][23].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…To our knowledge, no other study has looked at regional differences in autopsy rates among young sudden unexpected death cases, but one previous study from Ireland reported an autopsy rate in young sudden unexpected death cases to be 76%, which is similar to ours, 75% [1,4]. In our study of SCD in the young, we found the incidence rate to be higher than previously reported (2.8 per 100,000 person-years vs. 1.0-1.9 per 100,000 personyears in Italy, Netherlands, and UK) when including the non-autopsied cases [1,[21][22][23].…”
Section: Discussionsupporting
confidence: 87%
“…Autopsy may reveal structural heart diseases like hypertrophic or dilated cardiomyopathy, arrhythmogenic right ventricular cardiomyopathy, or myocardial infarction. However, in many cases, autopsy will show a structurally normal heart and no plausible explanation of the death [1][2][3][4]. These deaths-termed Sudden Unexplained Deaths (SUD)-have previously been shown to be associated with mutations in genes encoding cardiac ion channels in about 20% of cases [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…9,[15][16][17] In approximately 18%, autopsy does not reveal any structural cardiac disease, making this SUD. The application of a 24-hour time frame between the onset of complaints and the event or any other than the usual definition of SD reduces the proportion of cardiac causes (Table 2 and Figure 1).…”
Section: Clinicopathologically Assessed Seriesmentioning
confidence: 99%
“…The application of a 24-hour time frame between the onset of complaints and the event or any other than the usual definition of SD reduces the proportion of cardiac causes (Table 2 and Figure 1). 5,9,[15][16][17][18][19][20] Within the 1-to 40-year age group, the proportion of SCD, noncardiac SD, and SUD probably differs by age. Because the incidence of premature CAD gradually increases with age, the proportion of other cardiac causes of SD is presumably higher in the lower age groups.…”
Section: Clinicopathologically Assessed Seriesmentioning
confidence: 99%
“…1 Competing risks of sudden death in the young depend on age, but range from 0.09 per 1000 patient-years (age 0-35 years) to 0.13 per 1000 patient-years (age 35-49 years). [1][2][3][4][5] Unlike patients without WPW, atrial fibrillation (AF) in the presence of a rapidly conducting accessory pathway (AP) can result in a rapid ventricular response and ultimately degeneration to ventricular fibrillation (VF) with hemodynamic collapse. Thus, it is the inherent properties of the AP that determine the risk estimated by the shortest preexcited RR intervals during AF (SPRRI) or the AP effective refractory period (ERP) less than 250 milliseconds as the best known measures of risk.…”
Section: Introductionmentioning
confidence: 99%